TEACHERS’ ENGAGEMENT WITH WORK AND THEIR PSYCHOLOGICAL WELL-BEING - Ilisko, Dzintra; Badjanova, Jeļena; Ignatjeva, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
A number of studies are focusing on interrelations that exist between teachers’ subjective well-being and financial well-being, occupational stress and other factors that influence teachers’ happiness at work. The aim of this study is to explore the factors influencing teachers’ psychological well-being. This involves teachers’ engagement with their professional development. Psychological well-being is conceptualized as a psychological state of mind of teachers in balancing expectations and ability to meet those requirements, a desire for a mindful and meaningful involvement with their work, as well as resilience and competency to deal with the challenging requirements at the workplace. Teachers’ well-being and happiness at work positively influences their performance and a well-being of pupils as well. As a rule, teachers’ profession is associated with high stress, heavy workload, high demands on management in the classroom, high demands on pupils’ academic achievements, and the additional pressure placed on teachers’ engagement with further education. The authors carried out a questionnaire among the teachers from Latvia (n=247). They filled in a questionnaire on a voluntary basis about their subjective well-being in relations to their involvement with the pedagogical work. The authors explored correlation between teachers’ engagement with the research, their educational level, involvement in administrative work, teachers’ personal growth, their view on pupils as open systems and their well-being. It was concluded that all teachers who took part in this study is a relatively homogenous group. Considering their diverse experience of work, educational level and involvement with the scientific and administrative work, their psychological wellbeing can be evaluated higher as average.